STAGES OF THE PROCESS OF TEACHING PRIMARY SCHOOL STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the main stages of the teaching process of primary school students based on the age characteristics of primary school students. The importance of logical chain in the educational process from the perception of knowledge to its application in practice is highlighted.